Drowning in data, thirsty for information and starved for understanding: A biodiversity information hub for cooperative environmental monitoring in South Africa. (October 2022) - MacFadyen, Sandra; Allsopp, Nicky; Altwegg, Res; Archibald, Sally; Botha, Judith; Bradshaw, Karen; Carruthers, Jane; De Klerk, Helen; de Vos, Alta; Distiller, Greg; Foord, Stefan; Freitag-Ronaldson, Stefanie; et al.
Abstract: The world is firmly cemented in a notitian age (Latin: notitia, meaning data) – drowning in data, yet thirsty for information and the synthesis of knowledge into understanding. As concerns over biodiversity declines escalate, the volume, diversity and speed at which new environmental and ecological data are generated has increased exponentially. Data availability primes the research and discovery engine driving biodiversity conservation. South Africa (SA) is poised to become a world leader in biodiversity conservation. However, continent-wide resource limitations hamper the establishment of inclusive technologies and robust platforms and tools for biodiversity informatics. In this perspectives piece, we bring together the opinions of 37 co-authors from 20 different departments, across 10 SA universities, 7 national and provincial conservation research agencies, and various institutes and private conservation, research and management bodies, to develop a way forward for biodiversity informatics in SA. We propose the development of a SA Biodiversity Informatics Hub and describe the essential components necessary for its design, implementation and sustainability. We emphasise the importance of developing a culture of cooperation, collaboration and interoperability among custodians of biodiversity data to establish operational workflows for data synthesis. However, our biggest challenges are misgivings around data sharing and multidisciplinary collaboration. We recommend a system that is free, user friendly, functional, stable, integrative and designed to cater for different data access agreement levels. Sharing data through this pipeline will directly advance the science and practice of conservation, giving multiple stakeholders and decision-makers access to valuable biodiversity data to support research and biodiversity conservation. Graphical abstract: Unlabelled Image Highlights: Challenges and opportunities for Biodiversity Informatics in South Africa Misgivings around data sharing and multidisciplinary collaboration to leverage combined expertise Culture of cooperation, collaboration, interoperability to establish operational workflows for biodiversity data synthesis Local systems to link with global networks for an interconnected digital biodiversity knowledgebase SA-BioInfo-Hub: Free, user friendly, functional, stable, integrative system with varied access agreement levels